Reality of premature ovarian failure in Argentina - Demayo,Sandra (2019)
SUMMARY Premature Ovarian Insufficiency is defined as a decline in ovarian function that is accompanied by two biochemical determinations of Follicle Stimulating Hormone in hypergonadotropic values, in addition to low levels of circulating estrogens in women under 40 years old. Although some of its possible etiologies are recognized and diagnosed, most of the time, its cause remains unknown. It is a pathology with medical, psychological, and reproductive implications. Patients may experience climacteric symptoms, infertility, and emotional distress. In the medium and long term, cardiovascular and bone health can be affected, and some degree of cognitive deterioration can be evidenced. The therapeutic approach needs to be comprehensive for the patient and multidisciplinary. SAEGRE created in Argentina an interhospital network dedicated to gathering relevant statistical information regarding this and other pathologies in order to provide better assistance for these patients.